Asthma management pocket reference 2008 - van Weel, C; Bateman, E.D; Bousquet, J; Reid, J; Grouse, L; Schermer, T; Valovirta, E; Zhong, N (Allergy (Copenhagen), 2008)
Asthma is one of the most common chronic airways diseases worldwide, and its prevalence is increasing. Family doctors (sometimes called 'primary care physicians' or 'general practitioners') are frequently an asthma patient's first point of contact with healthcare systems. Disease management that follows evidence-based practice guidelines yields better patient results, but such guidelines are often complicated and may recommend the use of resources not available in the family practice setting. A joint expert panel of the World Organization of Family Doctors (Wonca), International Primary Care Airways Group (IPAG) and the International Primary Care Respiratory Group (IPCRG) offers support to family doctors worldwide by distilling the globally accepted, evidence-based recommendations from the Global Initiative for Asthma (GINA) into this brief reference guide. This guide provides tools intended to supplement a thorough history taking and the clinician's professional judgment in order to provide the best possible care for patients with asthma. Diagnostic Questionnaires developed for children and adults specifically focus the physician's attention on key symptoms and markers of asthma. When questionnaire responses suggest a diagnosis of asthma, Diagnosis Guides then lead the clinician through a series of investigations commonly available in primary care to support the diagnosis. In patients >40 years who smoke, COPD is an important alternative diagnosis, and some key aspects of differential diagnosis are illuminated. According to GINA, the goal of asthma treatment is to achieve and maintain control of the disease symptoms long-term. The physician must first assess the patient's current level of asthma control, then treat asthma in a stepwise manner to achieve and maintain symptom control. Both of these aspects are summarized in figures included in this guide. Finally, the guide also presents a flow chart summarizing management of asthma exacerbations in the acute care setting, and a glossary of asthma medications to assist the clinician in making medication choices for each individual patient. Finally, many patients with asthma also have concomitant allergic rhinitis, and this must be checked. The World Organization of Family Doctors has been delegated by WHO as the group that will be taking primary responsibility for education about chronic respiratory diseases among primary care physicians globally. This document will be a major resource in this educational program.